THE RELATIONSHIP OF TYPE OF PERSONALIT (EXTROVERT AND INTROVERT) WITH THE LEVEL OF DEPRESSION OF ELDERLY IN WERDHA BINA BHAKTI SERPONG 2020 - Nerli Adria Sinabutar; Tri Widiastuti; Tantri Wenny Sitanggang (Jurnal Kesehatan STIKes IMC Bintaro, 2020)
The large number of elderly population in Indonesia in the future has both positive and negative impacts. Positive if the elderly are in a productive state, and negative if the elderly are in a state of illness. Elderly is a group vulnerable to physical and psychological changes. One that often happens is depression. Depression is a feeling of sadness associated with suffering, and one of the elderly depression factors is personality, namely introverts and extroverts.The purpose of this study is to determine the relationship between personality types and the level of depression in the elderly at the Nursing Home at Bina Bhakti Serpong in 2020. This study unsing an elderly people as sample 60 years. Using a correlation analytic with a cross-sectional desain study using a quota sampling to catch a sample.Based on the research, it was found that the majority of residents of werdha bina serpong nursing homes were the average female sex (55.4%), marital status with widows / widowers (55.4%), primary education (42.9%), average age 60-74 years (66.1%), have introverted personality (50%) and mild depression (58.9%), non-mild depression (41.1%). Bivariate test in this study has a personality relationship with the level of depression, where the p-value = 0.001, CI lower 1.525 and upper 4.664. The prevalence ratio shows 2,667 which means extroverted personality has a chance of experiencing mild depression (85.7%) compared to introverted personality. Based on the results of these studies it is recommended to provide more frequent routine activities undertaken by the elderly so that good communication is established and can increase the stimulus of the elderly in interacting with others.